Acute Toxicity Test and Behavioural Activity of Aqueous and Ethanol Dried Leaf Extracts of Solenostemon monostachyus In Mice (Nigerian Journal of Pharmaceutical Research, 2022)
Background: The leaves of Solenostemon monostachyus have been traditionally used for various medicinal purposes, including CNS related ailments.Objective: To evaluate the median lethal dose (LD50), behavioural activity with possible mechanism(s) of action of aqueous dried leaf extract (AESM) and ethanol dried leaf extract (EESM) of Solenostemon monostachyus                    Method: The aqueous and ethanol extracts were obtained using sohxlet extraction and 80% ethanol respectively. The LD50 of the extracts was determined orally (p.o.) and intraperitoneally (i.p.). The effects of the AESM and EESM (200, 400, 800 mg/kg, p.o., n=6) on novelty-induced behaviours (NIB) were evaluated using the open field test. Possible mechanism(s) were evaluated using antagonists: flumazenil, naloxone and cyproheptadine at 2 mg/kg each, atropine and yohimbine at 1 mg/kg each.                                       Results: The LD50 values obtained for AESM and EESM were 3808 and 2154 mg/kg p.o. respectively, while i.p., values were 490 and 693 mg/kg respectively. AESM and EESM (200, 400, 800 mg/kg, p.o.)  significantly (p < 0.05) reduced the NIB. The probable pathways could be majorly facilitated through adrenergic, and GABAergic pathways, though the serotonergic, opioidergic and muscarinic pathways may be implicated. These pathways, except the muscarinic pathway may be implicated in the action of EESM.                                                                 Conclusion: The aqueous and ethanol dried leaf extracts of S. monostachyus showed slight and moderate toxicity respectively, suppressed CNS which could be mediated mainly through antagonism of adrenergic and augmentation of GABAergic neurotransmission, while cholinergic (except EESM), opioidergic and serotonergic pathways may be involved.